Analisis Penerapan Bunga Tunggal Dan Bunga Majemuk pada Koperasi Simpan Pinjam - Sintraka Kesumat Wargani; Anjela Safira; Sopie Halimah; Aziza Fajriah; Meirina Risma (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This study aims to analyze the application of single interest and compound interest in savings and loan cooperatives. Interest is an important aspect of savings and loan cooperative operations that can affect cooperative finances and member satisfaction. In this study, an analysis was carried out on the differences between the application of single interest and compound interest and their impact on savings and loan cooperatives. The research method used is literature study and comparative analysis. Data were obtained from primary and secondary sources which included cooperative documents, related literature, and interviews with cooperative management. The results of the study show that the application of single interest and compound interest has different implications for cooperative finance and member satisfaction. The conclusion of this study is the importance of savings and loan cooperatives considering factors such as the characteristics of the members, the goals of the cooperative, and the clarity of calculations in choosing the type of interest to be applied. Education to members about the difference between single interest and compound interest and their implications is also an important factor in the successful application of interest in savings and loan cooperatives.